VDAC1 as Pharmacological Target in Cancer and Neurodegeneration: Focus on Its Role in Apoptosis - Magrì, Andrea; Reina, Simona; De Pinto, Vito (Frontiers in Chemistry, 2018)
Cancer and neurodegeneration are different classes of diseases that share the involvement of mitochondria in their pathogenesis. Whereas the high glycolytic rate (the so-called Warburg metabolism) and the suppression of apoptosis are key elements for the establishment and maintenance of cancer cells, mitochondrial dysfunction and increased cell death mark neurodegeneration. As a main actor in the regulation of cell metabolism and apoptosis, VDAC may represent the common point between these two broad families of pathologies. Located in the outer mitochondrial membrane, VDAC forms channels that control the flux of ions and metabolites across the mitochondrion thus mediating the organelle's cross-talk with the rest of the cell. Furthermore, the interaction with both pro-apoptotic and anti-apoptotic factors makes VDAC a gatekeeper for mitochondria-mediated cell death and survival signaling pathways. Unfortunately, the lack of an evident druggability of this protein, since it has no defined binding or active sites, makes the quest for VDAC interacting molecules a difficult tale. Pharmacologically active molecules of different classes have been proposed to hit cancer and neurodegeneration. In this work, we provide an exhaustive and detailed survey of all the molecules, peptides and microRNAs that exploit VDAC in the treatment of the two examined classes of pathologies. The mechanism of action and the potential or effectiveness of each compound are discussed.